Activism and the American novel : religion and resistance in fiction by women of color - Romero, Channette (University of Virginia Press, 2012)
"Since the 1980s, many activists and writers have turned from identity politics toward ethnic religious traditions to rediscover and reinvigorate their historic role in resistance to colonialism and oppression. In her examination of contemporary fiction by women of color--including Toni Morrison, Ana Castillo, Toni Cade Bambara, Louise Erdrich, and Leslie Marmon Silko--Channette Romero considers the way these novels newly engage with Vodun, Santería, Candomblé, and American Indian traditions. Critical of a widespread disengagement from civic participation and of the contemporary novel's disconnection from politics, this fiction attempts to transform the novel and the practice of reading into a means of political engagement and an inspiration for social change."--Project Muse.